The Valuation of Stock Options - Bierman, Harold (Journal of Financial and Quantitative Analysis, 1967)
There is little question that stock options have value, but there is considerable question as to how stock options should be valued. Persons studying the valuation question and writing in business periodicals have tied the value of the stock option to the expected or the actual appreciation in the value of the stock.